Transcranial physical methods for correction of neuroendocrine and cerebral disorders in adolescent girls with obesity - Bolotova, N V; Aver'ianov, A P; Dronova, E G; Raĭgorodskiĭ, Iu M; Levit, S V (Terapevtic̆eskii arhiv, 2012)
To evaluate the efficiency of combined central and local physiotherapeutic procedures in correcting neuroendocrine and menstrual disorders in pubertal girls (PG) with obesity. Eighty-seven PGs, including 67 with different levels of obesity and 20 healthy non-obese girls, were examined. The hormonal profile, lipidogram, and fasting insulin and glucose levels were studied. Body mass index (BMI) and waist and hip circumferences were estimated. The functional state of the central nervous system was studied by electroencephalography. The parameters of the autonomic nervous system were estimated by cardiointervalography. The PGs with obesity were divided into 2 groups: a study group (SG) (n = 40) and a control group (CG) (n = 27). The healthy PGs (n = 20) formed a comparison group. The SG patients received bitemporal transcranial magnetic therapy in combination with frontomastoid transcranial electrostimulation, as well as myoelectrostimulation of the anterior abdominal wall, by transferring the area of stimulation from right to left hypochondrium. A course consisted of 10-15 daily sessions. CG had placebo physioprocedures (with disconnected electrodes). After 6-month treatment, SG and CG showed average reductions in BMI by 5.9 and 2.5 kg/m2, respectively. Lipidograms normalized in 70%; menstrual cycles were restored in 25 of 30 patients with impaired cycles in SG and in 1 of 22 in CG. Hormonal profiles were significantly improved in 62.5% of the patients in SG and unchanged in CG. The high efficiency of combined (central and local) physiotherapeutic procedures is likely to be dueto the normalization of pituitary-ovarian relationships and enables one to recommend the proposed procedure in a rehabilitation program for PGs with obesity and reproductive system disorders.